The Elaboration of Persuasive Health Protocol Messages During The Adaptation of New Habits of Covid-19 - Azis, Hasbullah; Peni Indreswari, Esfandani (ETTISAL : Journal of Communication, 2024)
The increasing number of victims caused by COVID-19 has driven the Indonesian government to implement policies for COVID-19 handling and prevention through various strategies, one of which is implementing health protocols. Advisory notices to follow health protocols were responded to by the public with multiple attitudes, such as compliance and rejection. Young people are believed to have low compliance and tend to ignore health behavior, especially during the COVID-19 pandemic. By using the Elaboration Likelihood theoretical approach, this study aimed to identify the extent to which young people process adherence messages of health protocols during the COVID-19 pandemic delivered by the Indonesian government. As many as 174 young people were surveyed and found that health protocols were applied through central dan peripheral channels simultaneously. The messages are conveyed elaborately in a simple and less critical matter.